Synthesis and Biological Activity of Some new 2-Heterocyclic/acyclic amino/4'-acetamidophenoxy-3-(4-chloro-phenyl)-3, 4-dihydrobenzo[e]- [1,3,2]oxazaphosphinine 2-sulfides - K. R. Kishore Kumar Reddy (E-Journal of Chemistry, 2008)
2-Heterocyclic/acyclicamino/4'-acetamidophenoxy-3-(4-chlorophenyl)-3,4-dihydrobenzo-[e][1,3,2]oxazaphosphinine 2-sulfides (4a-j) were synthesized through a two steps process. In the first step, 2-chloro-3-(4-chlorophenyl)-3, 4-dihydrobenzo[e] [1,3,2]-oxazaphosphinine 2-sulfide (2) was prepared by the reaction of 2-[(4-chlorophenylamino)methyl]phenol (1) with thiophosphoryl chloride in the presence of triethylamine in dry toluene-tetrahydrofuran. In the second step, 2 was treated with various heterocyclic/acyclicamines/4'-acetamidophenol in presence of triethylamine-/ sodium hydride in toluene-tetrahydrofuran at 45-50°C . All the synthesized compounds (4a-j) were characterized by elemental analysis, IR, NMR(1H, 13C and 31P) and mass spectra and their biological activity was evaluated for antimicrobial activity.